2016
DOI: 10.12945/j.aorta.2016.15.022
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous origin of the left vertebral artery from the aortic arch

Abstract: Anatomic anomalies of the aortic arch have implications for clinical practice if their significance is understood. Our case study involves a cadaveric finding of the left vertebral artery originating directly from the aortic arch. Although this anatomical variation has been documented, the prevalence of this anomaly may be generally underestimated. After noting this anomaly, we analyzed 27 cases and found that four female cadavers had the left vertebral artery originating from the aortic arch rather than the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 6 publications
1
12
0
Order By: Relevance
“…So the prevalence rate comes to 14.8 %, and concluded that this anomaly is more prevalent than thought earlier, and may have implications for surgical practice. (10) We also noted this finding in one of our cases. A series of 216 patients with TOF was investigated by catheterization, and post catheterization analysis was done by Sadia Saeed et al They found Pulmonary Artery (PA) abnormalities in 84 (38.9%) patients.…”
Section: Aberrant Vesselssupporting
confidence: 75%
“…So the prevalence rate comes to 14.8 %, and concluded that this anomaly is more prevalent than thought earlier, and may have implications for surgical practice. (10) We also noted this finding in one of our cases. A series of 216 patients with TOF was investigated by catheterization, and post catheterization analysis was done by Sadia Saeed et al They found Pulmonary Artery (PA) abnormalities in 84 (38.9%) patients.…”
Section: Aberrant Vesselssupporting
confidence: 75%
“…Budhiraja et al (2013) [8] assumed that the first part of VA could be the preserved left sixth segmental artery, or there might be a large absorption of the embryonic tissue of LSCA, between the origin of the AA to the origin of VA, causing direct origin of the LVA from the AA. The sixth cervical intersegmental artery customarily vanishes, but Einstein et al (2016) [15] supposed that it might have maintained, permitting blood flow from the arch of aorta. The cause of origin of the LVA from the AA might be the decreased blood flow through the normal origin of the LVA which is the dorsal division of the seventh cervical intersegmental artery.…”
Section: Discussionmentioning
confidence: 99%
“…The relatively benign nature of this anatomical variation may be contributing to an underestimated frequency. However, the fact that this variant appears to be more frequent in females than males [2] and as sex-based differences in pain perception by medical professionals has been recorded [12] we must consider the possibility that this variant underlies conditions that are being overlooked by health care providers. Improving our understanding of the frequency of this variant and educating health care practitioners to its possible presence could improve the quality of health care for many people.…”
Section: Discussionmentioning
confidence: 99%
“…I n typical human anatomy, the vertebral arteries (VA) originate from the subclavian arteries (SCA), enter the transverse foramen of the sixth cervical vertebra (C6), and travel within the subsequent more superior transverse foramina to enter the skull via the foramen magnum, and provide circulation to the posterior brain. Reported frequencies of VAs with aberrant origins vary widely, and have been reported in anywhere from 5 to 50% of the population [1][2][3]. Of those, left vertebral artery (LVA) variants are most common, appearing in approximately 2 to 7% of the population (as reported in a recent aggregation of studies) [1].…”
Section: Introductionmentioning
confidence: 99%